Analysis of Islamic Value in Learning Mathematics Era 4.0 - Bayu Mukti Abdullah; Budi Murtiyasa; Djalal Fuadi (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
The challenge of education today is a generation that is starting to weaken its work ethic and religisitas. This makes teachers need to equip students with material that is integrated with Islamic values, including in mathematics learning. The purpose of this study is to describe Islamic values in mathematics learning in the era of 4.0 by knowing how to implement it and mathematical topics that can be integrated with Islamic values. The research subjects consisted of mathematics subject teachers and students. Through observations and interviews, it was found that Islamic values of patience, honesty, never giving up and tawakkal were integrated in mathematics learning. The implementation of Islamic values is carried out by linking mathematics learning materials with the content of the verses of the al-Qur'anÂ